2021
DOI: 10.1136/bmj.n2026
|View full text |Cite
|
Sign up to set email alerts
|

Advances in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is an uncommon but potentially catastrophic diagnosis with historically high mortality rates. The standard of care treatment remained unchanged for decades; however, recent discoveries of molecular drivers of leukemogenesis and disease progression have led to novel therapies for AML. Ongoing research and clinical trials are actively seeking to personalize therapy by identifying molecular targets, discovering patient specific and disease specific risk factors, and identifying effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
174
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(199 citation statements)
references
References 193 publications
0
174
0
2
Order By: Relevance
“…Acute myeloid leukemia (AML) is an aggressive malignant neoplasm arising within bone marrow, characterized by aberrant accumulation of myeloid precursors (Lim et al, 2017). As a deadliest form of acute leukemia, patients with AML have a dismal 5-year survival rate of 28.3%, and most cases still relapse frequently after remission, leading to a poor prognosis (Lewis et al, 2021;Newell and Cook, 2021). Recently, it is demonstrated that the molecular genetic abnormalities are significantly associated with prognosis in AML, which can serve as a comprehensive risk-stratification system and an effective therapy option (Bernard et al, 2020;Dohner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is an aggressive malignant neoplasm arising within bone marrow, characterized by aberrant accumulation of myeloid precursors (Lim et al, 2017). As a deadliest form of acute leukemia, patients with AML have a dismal 5-year survival rate of 28.3%, and most cases still relapse frequently after remission, leading to a poor prognosis (Lewis et al, 2021;Newell and Cook, 2021). Recently, it is demonstrated that the molecular genetic abnormalities are significantly associated with prognosis in AML, which can serve as a comprehensive risk-stratification system and an effective therapy option (Bernard et al, 2020;Dohner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…AML is a hematologic malignancy characterized by the proliferation of immature myeloid cells [ 3 ]. The five-year survival for AML patients is approximately 30%, indicating poor outcomes for the AML patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently several targeted therapies for better efficacy and less toxicity were developed. Venetoclax, with a mechanism B cell lymphoma-2 (BCL-2) inhibition, ivosidenib and enasidenib inhibiting isocitrate dehydrogenase activity, glasdegib that inhibits the hedgehog pathway, and Fms-like tyrosine kinase 3 (FLT3) inhibitors are new agents for the treatment of a subset of AML [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a hematologic malignant disease that is characterized by the disruption of myeloid differentiation and an abnormal proliferation of myeloid precursor cells (Newell and Cook, 2021). The incidence of AML accounts for 10-20% of leukemia in children and the 5-years survival rate for AML is only about 30% in adults (Döhner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%